2023
DOI: 10.1055/s-0043-1771454
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Thrombectomy for Anterior Circulation Large Vessel Occlusion Stroke: An Evolution of Trials

Natalia Starikova,
Silja Räty,
Daniel Strbian
et al.

Abstract: The last decade's progress in demonstrating the clinical benefit of endovascular thrombectomy (EVT) in patients with large vessel occlusion stroke has transformed the paradigm of care for these patients. This review presents the milestones in implementing EVT as standard of care, demonstrates the current state of evidence, provides guidance for identifying the candidate patient for EVT, and highlights unsolved and controversial issues. Ongoing trials investigate broadening of EVT indications for patients who p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 143 publications
(152 reference statements)
0
10
0
Order By: Relevance
“…T he benefit of endovascular therapy (EVT) for patients with acute anterior circulation large vessel occlusion (LVO) with large infarct has been proven by 4 randomized clinical trials (RCTs). [1][2][3][4][5][6] The mechanical thrombectomy for large brain infarctions (MAGNA) individual patient-level data meta-analysis of 3 RCTs (Recovery by Endovascular Salvage for Cerebral Ultra-Acute Embolism-Japan Large Ischemic Core Trial [RESCUE-Japan LIMIT], 5 Randomized Controlled Trial to Optimize Patient's Selection for Endovascular Treatment in Acute Ischemic Stroke [SELECT2], 4 and Endovascular Therapy in Acute Anterior Circulation Large Vessel Occlusive Patients With a Large Infarct Core [ANGEL-ASPECT] 3 ) presented at the European Stroke Conference (ESOC) 2023 7 and 2 other study-level meta-analyses including RCTs and observational studies 8,9 also confirmed the efficacy of EVT for such patients. However, the Thrombectomy for Emergent Salvage of Large Anterior Circulation Ischemic Stroke (TESLA) RCT presented at ESOC 2023 did not demonstrate that EVT was superior to medical management for such patients according to the utility-weighted modified Rankin Scale (mRS) at 90 days, falling just short of the prespecified primary outcome threshold to confirm efficacy.…”
mentioning
confidence: 99%
“…T he benefit of endovascular therapy (EVT) for patients with acute anterior circulation large vessel occlusion (LVO) with large infarct has been proven by 4 randomized clinical trials (RCTs). [1][2][3][4][5][6] The mechanical thrombectomy for large brain infarctions (MAGNA) individual patient-level data meta-analysis of 3 RCTs (Recovery by Endovascular Salvage for Cerebral Ultra-Acute Embolism-Japan Large Ischemic Core Trial [RESCUE-Japan LIMIT], 5 Randomized Controlled Trial to Optimize Patient's Selection for Endovascular Treatment in Acute Ischemic Stroke [SELECT2], 4 and Endovascular Therapy in Acute Anterior Circulation Large Vessel Occlusive Patients With a Large Infarct Core [ANGEL-ASPECT] 3 ) presented at the European Stroke Conference (ESOC) 2023 7 and 2 other study-level meta-analyses including RCTs and observational studies 8,9 also confirmed the efficacy of EVT for such patients. However, the Thrombectomy for Emergent Salvage of Large Anterior Circulation Ischemic Stroke (TESLA) RCT presented at ESOC 2023 did not demonstrate that EVT was superior to medical management for such patients according to the utility-weighted modified Rankin Scale (mRS) at 90 days, falling just short of the prespecified primary outcome threshold to confirm efficacy.…”
mentioning
confidence: 99%
“…We enrolled adult patients with anterior circulation AIS undergoing EVT from January 2018 to January 2023. The inclusion criteria were as follows: (1) evidence of primary isolated MeVO or secondary MeVO after thrombectomy of MCA-M1 occlusion; (2) patients who received EVT, including stent retriever, aspiration, intra-arterial thrombolysis, rescue balloon or stenting angioplasty; and (3) mRS ≤ 2 before stroke onset. Patients with internal carotid artery occlusion, MCA-M1 occlusion, bilateral infarction, missing procedural details, premorbid mRS > 2, or mRS data missing were excluded from our study.…”
Section: Patients and Designmentioning
confidence: 99%
“…118 Improvements of the previously mentioned points resulted in five positive trials, MR CLEAN, ESCAPE, SWIFT-PRIME, EXTEND IA, REVASCAT, and THRACE in favor of intervention. 119 DAWN and DEFUSE-3 then extended the therapeutic window up to 24 hours. 120,121 These trials transformed stroke care with disability improvement in patients with the most morbid of strokes.…”
Section: Ischemic Strokementioning
confidence: 99%